Mechanisms underlying azimuth selectivity in the auditory cortex of the pallid bat - Razak, K.A. (2012)
This study focused on mechanisms underlying azimuth selectivity in the primary auditory cortex (A1) of pallid bats. The pallid bat listens to prey-generated noise (5–35 kHz) to localize and hunt terrestrial prey. The region of A1 tuned between 5–35 kHz consists of two clusters of neurons distinguished by interaural intensity difference (IID) selectivity: binaurally inhibited (EI) and peaked. The first aim of this study was to use sequential dichotic/free-field stimulation to test the hypothesis that IID is the primary cue underlying azimuth selectivity in neurons tuned in the prey-generated noise frequency band. IID selectivity and ear directionality at the neuron’s characteristic frequency (CF) were used to predict azimuth selectivity functions. The predicted azimuth selectivity was compared with the actual azimuth selectivity from the same neurons. Prediction accuracy was similarly high for EI neurons and peaked neurons with low CF, whereas predictions were increasingly inaccurate with increasing CF among the peaked neurons. The second aim of this study was to compare azimuth selectivity obtained with noise and CF tones to determine the extent to which stimulus bandwidth influences azimuth selectivity in neurons with different binaural properties. The azimuth selectivity functions were similar for the two stimuli in the majority of EI neurons. A greater percentage of peaked neurons showed differences in their azimuth selectivity for noise and tones. This included neurons with multiple peaks when tested with tones and a single peak when tested with noise. Taken together, data from the two aims suggest that azimuth tuning of EI neurons is primarily dictated by IID sensitivity at CF. Peaked neurons, particularly those with high CF, may integrate IID sensitivity across frequency to generate azimuth selectivity for broadband sound. The data are consistent with those found in cat and ferret A1 in that binaurally facilitated neurons depend to a greater extent (compared to EI neurons) on spectral integration of binaural properties to generate azimuth selectivity for broadband stimuli.